Jio and Reliance Retail announce JioPhone - Reliance Industries Limited (2022)
Jio and Reliance Retail announce JioPhone, smart feature phone, an unmatched Indian innovation. Made in India, by Indians and for all Indians. In less than a year since Jio’s launch, India zooms to NUMBER ONE from 155th in mobile data consumption in the world.